Effect of sublethal doses of the insecticide imidacloprid on adaptive traits of Drosophila melanogaster: Response to treatment over and after 15 consecutive generations - Patarro, Thais de França [UNESP]; Manzato, Antonio José [UNESP]; Madi-Ravazzi, Lilian [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP] (Scientific Research Publishing, 2013)
A sublethal dose of Imidacloprid, considered actually as the most widely used insecticide against biting and sucking insects, was administered to Drosophila melanogaster for detecting effects on biological traits. The choice of this species as organism-model potentially opens the possibility to explore more deeply the processes involved in those effects because, among other reasons, there is a large accumulation of biological knowledge on this species and because it propitiates multiple approaches in laboratory and nature. The flies were treated along 15 consecutive generations. F1 parents were randomly taken among virgin flies from the stocks, but the parents of the successive generations were the first 15 couples emerged in the previous one. The number of progeny (productivity) and the duration of the emergence period were analyzed in every generation revealing insecticide toxicity in 12 of the 15 generations. The observation of an increase in the number of progeny over the generations, which occurred in both control and treated experiments (although maintaining higher productivity in the control), suggested an effect of the use of the first 15 emerged couples in successive generations. A comparative analysis of the mortality of the F15 adult flies exposed to imidacloprid by contact, which involved flies from the control, treatment and from the stocks that originated the experiments, reinforced this idea, indicating a genetic interplay of the emergence speed with productivity and adult tolerance to the insecticide, a subject that may be better explored in another study. Toxicity was also observed for the traits longevity, viability during development from egg to adult and oviposition rate. Considering the present intensive use of imidacloprid, the harmful effects observed in these important biological characteristics may be considered able to decrease the adaptive value of D. melanogaster populations exposing them at risk of decline.
Keywords: Productivity; Longevity; Emergence Time Period; Egg-Adult Viability; Oviposition; Tolerance